Assessment of a double freezing approach in the management of surplus embryos in IVF. Issue 4 (April 2019) - Farhi, Jacob; Elizur, Shai; Yonish, Michal; Seidman, Daniel S; Shulman, Adrian; Schiff, Eyal; Orvieto, Raoul
Abstract: Research question: What pregnancy rates are achieved after transfer of cryopreserved double slow-frozen embryos in IVF cycles? Patients in whom surplus thawed cleaved embryos (day 2 or 3) were grown to the blastocyst stage, re-frozen and then re-thawed for transfer (double freezing) were included. Design: Data were collected on all patients who had undergone the above procedure at the IVF unit of Assuta Ramat Hachayal Hospital, Tel Aviv, during a 7-year period. For each patient in the study group, the two-consecutive, matched-by-age patients treated with frozen–thawed single blastocyst transfer were selected to form a 2:1 ratio control group. All embryos were frozen using the slow freeze protocol. Results: A total of 54 patients had 70 embryos that were re-frozen at the blastocyst stage. Twenty-eight of these blastocysts were thawed and 27 underwent transfer to 25 patients. A single embryo was transferred to 23 patients and two embryos were transferred to two patients. The survival rate of the second thawing was 96.4% (27/28). Clinical pregnancy rate was 16% (4/25) and implantation rate was 14.8% (4/27). In the study group, pregnancies were achieved in 22 out of the 25 patients using IVF treatment, indicating good receptivity of the uterus. In the control group, the implantation/pregnancy rates were significantly higher (44.2% [23/52]; P < 0.01). Conclusion: The transfer of twice slow-frozen and thawed embryos does not seem to be a beneficial approach in the planned management of cryopreserved surplus embryos owing to the low pregnancy rate achieved after transfer of the re-frozen blastocyst embryos.